Bryozoa of Floridan Oculina reefs - Winston, Judith E. (Zootaxa, 2016)
The deep-water Oculina coral reefs on the continental shelf off the east central coast of Florida are a unique protected marine habitat. A complete inventory of the Oculina-associated fauna is important to support its conservation. This paper provides an inventory of the bryozoans of the Oculina reef area. Unusually, the bryozoan fauna is dominated by encrusting cribrilinid bryozoans. These include two new species of Puellina and three other Floridan-Atlantic shelf Puellina only recently described. Additional cribrilinid species belong to the genera Klugerella and Rosulapelta. Other bryozoans found in the habitat include 38 encrusting cheilostome species, six of them new to science, belonging to the genera Callopora, Parasmittina, Parasmittina, Smittina, Microporella and Stephanollona. Cyclostomes were only sparsely represented, comprising three encrusting taxa.